Electronics Are Leaving the Plane: Stacking chips and connecting them vertically increases both speed and functionality. - Monroe, Don (Communications of the ACM, 2018)
The article discusses the assembling the components of integrated circuits vertically on semiconductor three-dimensional 3D) chips (or stacking chips), including its role in improving computer performance and speed. An overview of high-bandwidth memory (HBM), including its memory in comparison with graphics processor units (GPUs), is provided.